Genealogy, epistemology and worldmaking - Srinivasan, A (Oxford University Press, 2019)
We suffer from genealogical anxiety when we worry that the contingent origins of our representations, once revealed, will somehow undermine or cast doubt on those representations. Is such anxiety ever rational? Many have apparently thought so, from pre-Socratic critics of Greek theology to contemporary evolutionary debunkers of morality. One strategy for vindicating critical genealogies is to see them as undermining the epistemic standing of our representations—the justification of our beliefs, the aptness of our concepts, and so on. I argue that this strategy is not as promising as it might first seem. Instead, I suggest that critical genealogies can wield a sort of meta-epistemic power; in so far as we wish to resist the genealogical critic, we are under pressure to see ourselves as the beneficiaries of a certain kind of good luck: what I call genealogical luck. But there is also a resolutely non-epistemic way of understanding the power of critical genealogies, one that is essential, I argue, for understanding the genealogical projects of various theorists, including Nietzsche and Catharine MacKinnon. For critical genealogies can reveal what it is that our representations do—and what we, in turn, might do with them.